Bill's Paper Chase : Lady of the Barge and Others, Part 3. - Jacobs, W. W. (William Wymark), 1863-1943; Greiffenhagen, Maurice, 1862-1931; Richards, Amy, active 1896-1918 (Salt Lake City, UT : Project Gutenberg, 2004)
"Bill's Paper Chase" by W. W. Jacobs is a humorous short story that is part of a collection of tales featuring maritime life and its colorful characters, written in the early 20th century. The narrative unfolds on a ship, where the protagonist, Bill, and his shipmates grapple with the unscrupulous ways of their fellow sailor, the miserly Thomas Geary, who clings fiercely to his savings. The story primarily explores themes of greed, deception, and the burgeoning camaraderie among sailors, capturing the essence of life at sea with its distinct challenges and moral complexities. The plot centers around Thomas Geary, whose fixation with his hard-earned money becomes tragically ironic when he falls ill and ultimately dies, leading to a wild scheme among the crew to recover the money he insisted he couldn't take with him. Bill, in particular, becomes fixated on the idea of finding Thomas's hidden wealth, bonding with a young boy aboard the ship named Jimmy in their underhanded dealings. As they devise a plan to retrieve the money, various mishaps and misunderstandings unfold, ultimately culminating in the disappearance of Jimmy and the elusive treasure. The tale is rich in witty dialogues and showcases Jacobs' knack for creating lively characters, deftly mixing humor with darker undertones of greed and the folly of misplaced priorities. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; River life -- Fiction